The Impact of Class and Sexuality-Based Stereotyping on Rape Blame. (19th April 2016) - Spencer, Bettina
In order to investigate whether stereotypes about sexuality can impact perceptions of sexual assault, participants read a scenario that described a situation in which a woman reported being raped. The woman's socioeconomic status (SES) was varied, so that she appeared to be of low or high-SES. Following the vignette, participants completed explicit measures that assessed victim blame, attitudes toward rape victims, and perceived promiscuity. Participants also answered an open-ended question that was coded for minimizing and maximizing language. Last, participants completed an "attitude survey" that measured classist attitudes. It was hypothesized that participants who read about the low-SES woman would show more rape blame, display more negative attitudes about rape victims, respond to the open-ended question with more minimizing language, and perceive her as being more promiscuous. It was also predicted that these explicit measures would be positively correlated and that the language measure would be moderated by participants' classism. Results supported these hypotheses. Participants who read about the low-SES survivor showed more negative attitudes, believed her to be more culpable, and more promiscuous. The explicit measures were positively correlated. Additionally, participants differed in linguistic minimization and maximization, such that participants who were low in classism were more likely to maximize the low-SES target's experience, whereas participants who were high in classism were more likely to minimize the low-SES target's experience. Taken together, these results suggest that low-SES women are stereotyped as being promiscuous and that this stereotype affects how they may be blamed after cases of sexual assault. Public Health Significance Statement: The results of this study suggest that low-socioeconomic status (SES) survivors of assault are more likely to be blamed and found culpable for the assault than high-SES women. These attitudes correlate with stereotypes about low-SES women's sexuality.